Consciousness explained better towards an integral understanding of the multifaceted nature of consciousness - Combs, Allan (Paragon House, 2009)
"Consciousness is explored as a living stream of lucid experience composed of the essence of the moments of our lives. Grounded in Ken Wilber's model, consciousness is explained from many points of view: its historical evolution, its growth in the individual, its mystical dimensions, and the meaning of enlightenment"--Provided by publisher.
"Consciousness is explored as a living stream of lucid experience composed of the essence of the moments of our lives. Grounded in Ken Wilber's model, consciousness is explained from many points of view: its historical evolution, its growth in the individual, its mystical dimensions, and the meaning of enlightenment"--Provided by publisher.
Includes bibliographical references
Keywords: Consciousness; Philosophie; Bewusstsein